CyberKnife Stereotactic Body Radiation Therapy as an Effective Treatment for Hepatocellular Carcinoma Patients With Decompensated Cirrhosis - Sun, Jing; Zhang, Aimin; Li, Wengang; Wang, Quan; Wang, Jia; Fan, Yuze; Sun, Yingzhe; Li, Dong; Zhang, Dan; Duan, Xuezhang (Frontiers in Oncology, 2020)
Purpose: The aim of our study was to evaluate the curative effect and safety of CyberKnife stereotactic body radiation therapy in treating decompensated cirrhosis hepatocellular carcinoma (HCC) patients. Methods: From March 2011 to December 2015, 32 HCC patients who refused or were ineligible for other treatments were treated with CyberKnife stereotactic body radiation therapy. Among these patients, 17 were Child-Pugh score 7 (53.13%), 7 were Child-Pugh score 8 (21.87%), 4 were Child-Pugh score 9 (12.50%), and 4 were Child-Pugh score 10 (12.50%). A total dose of 45–54 Gy in 5–10 fractions was given according to the location of lesions. Results: The median follow-up period was 30 months (8–46 months). By July 2019, the tumors were recurrent or metastasized in 17 patients. The overall survival rates of 1, 2, and 3 years were 84.4, 61.8, and 46.0%, respectively. After 1, 2, and 3 years, the local control rates were 92.9%. The progression-free survival rates of the 1, 2, and 3-year treatments were 73.8, 44.6, and 33.4%, respectively. Conclusions: CyberKnife stereotactic body radiation therapy was an effective option for HCC patients with decompensated cirrhosis. The liver injury occurrence rate was acceptable in our study.